PEMBERDAYAAN IBU BADUTA UNTUK PENINGKATAN MUTU MP-ASI BADUTA 12-24 BULAN DAN PELATIHAN MP-ASI BERBAHAN DASAR IKAN BANDENG (Chanos chanos) - Zuraidah, Yenni (Jurnal Pengabdian Kepada Masyarakat Pusat Unggulan Iptek Penanggulangan Stunting Berbasis Kesehatan Ibu dan Anak, 2025)
This Community Service activity is an application of the results of previous research community-based stunting prevention in children 0-6 months. The results show that the highest contributor to stunting is inadequate complementary food, not varying the type of ingredients and processing. The handling of stunting by the central government is mostly an aid program, which does not increase community knowledge and independence in solving problems. The purpose of this community service is to increase the knowledge of mothers of under-five children about the adequacy of the amount and type as well as the accuracy of complementary food provision and how to prepare healthy complementary food through the utilization of milkfish as a fish with a low price but high nutrition into various preparations The results of community service have understood the importance of preparing adequate complementary food for stunting prevention. The community has been able to make processed MP-ASI high in protein by utilizing abundant local food around them. The community is stimulated to be creative in creating other preparations and trained to develop products into businesses. The location of the village, which is a mangrove area and river estuary, is a potential fishery that is quite diverse and cheap prices can be made into various processed semi-finished complementary food ingredients that can even be made into a home industry business. It is necessary to cooperate with several related agencies for the development of semi-finished processed home industries of various fishery products. Keywords: Empowerment, complementary food, Children Under Two, milkfish